Achieving the excellent self-lubricity and low wear of TiAl intermetallics through the addition of copper coated graphite. (1st October 2020) - Wang, Long; Tieu, Anh Kiet; Zhu, Qiang; Chen, Jiao; Cheng, Jun; Yang, Jun; Kosasih, Buyung
Abstract: The present work achieves excellent lubricity and low wear of TiAl intermetallics by the addition of low-cost copper-coated graphite. 50% reduction of friction and more than one magnitude lower wear rate were obtained. This superior tribological property is attributed to the formation of a soft tribo-film and a synergetic effect of in-situ formed harder TiC reinforcement. This tribo-film contains some graphite nanoplatelets, shell-like carbon, TiC particles and the mixture of some oxides. This work is helpful not only for the development of new solid self-lubricating composites but also promotes a scientific understanding of the tribo-film of solid lubricants.